Breaching the limit: formation of GW190521-like and IMBH mergers in young massive clusters - Arca Sedda, Manuel; Rizzuto, Francesco Paolo; Naab, Thorsten; Ostriker, Jeremiah; Giersz, Mirek; Spurzem, Rainer (The astrophysical journal, 2021)
The LIGO-Virgo-Kagra Collaboration (LVC) discovered recently GW190521, a gravitational wave (GW) source associated with the merger between two black holes (BHs) with mass 66 and >85 M ⊙. GW190521 represents the first BH binary merger with a primary mass falling in the upper-mass gap and the first leaving behind an ∼150 M ⊙ remnant. So far, the LVC has reported the discovery of four further mergers having a total mass >100 M ⊙, i.e., in the intermediate-mass black hole (IMBH) mass range. Here, we discuss results from a series of 80 N-body simulations of young massive clusters that implement relativistic corrections to follow compact object mergers. We discover the development of a GW190521-like system as the result of a third-generation merger, and four IMBH-BH mergers with total mass (300-350)M ⊙. We show that these IMBH-BH mergers are low-frequency GW sources detectable with LISA and Deci-hertz Interferometer Gravitational wave Observatory (DECIGO) out to redshift z = 0.01-0.1 and z > 100, and we discuss how their detection could help unraveling IMBH natal spins. For the GW190521 test case, we show that the third-generation merger remnant has a spin and effective spin parameter that matches the 90% credible interval measured for GW190521 better than a simpler double merger and comparable to a single merger. Due to GW recoil kicks, we show that retaining the products of these mergers require birth sites with escape velocities ≳50-100 km s−1, values typically attained in galactic nuclei and massive clusters with steep density profiles.
Gesehen am 15.01.2022